Free Radical Oxidation of Antimicrobial Peptides in Phospholipid Membranes - Barrías-González, P; Mura-Mardones, F; Zapata-Lizama, M; Zapata-Lizama, M (ELSEVIER SCIENCE INC, 2023)
Sin Resumen Disponible